Comparative effectiveness and safety of pharmacological and non-pharmacological interventions for insomnia: an overview of reviews - Rios, Patricia; Cardoso, Roberta; Morra, Deanna; Nincic, Vera; Goodarzi, Zahra; Farah, Bechara; Harricharan, Sharada; Morin, Charles M; Leech, Judith; Straus, Sharon E; Tricco, Andrea C (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background This review aimed to assess the existing evidence regarding the clinical effectiveness and safety of pharmacological and non-pharmacological interventions in adults with insomnia and identify where research or policy development is needed. Methods MEDLINE, Embase, PsycINFO, The Cochrane Library, and PubMed were searched from inception until June 14, 2017, along with relevant gray literature sites. Two reviewers independently screened titles/abstracts and full-text articles, and a single reviewer with an independent verifier completed charting, data abstraction, and quality appraisal. Results A total of 64 systematic reviews (35 with meta-analysis) were included after screening 5024 titles and abstracts and 525 full-text articles. Eight of the included reviews were rated as high quality using the Assessment of Multiple Systematic Reviews 2 (AMSTAR2) tool, and over half of the included articles (n = 40) were rated as low or critically low quality. Consistent evidence of effectiveness across multiple outcomes based on more than one high- or moderate quality review with meta-analysis was found for zolpidem, suvorexant, doxepin, melatonin, and cognitive behavioral therapy (CBT), and evidence of effectiveness across multiple outcomes based on one high-quality review with meta-analysis was found for temazepam, triazolam, zopiclone, trazodone, and behavioral interventions. These interventions were mostly evaluated in the short term (< 16 weeks), and there was very little harms data available for the pharmacological interventions making it difficult to evaluate their risk-benefit ratio. Conclusions Assuming non-pharmacological interventions are preferable from a safety perspective CBT can be considered an effective first-line therapy for adults with insomnia followed by other behavioral interventions. Short courses of pharmacological interventions can be supplements to CBT or behavioral therapy; however, no evidence regarding the appropriate duration of pharmacological therapy is available from these reviews. Systematic review registration PROSPERO CRD42017072527.